2021
DOI: 10.1159/000513927
|View full text |Cite
|
Sign up to set email alerts
|

Preference, Adherence, and Maintenance of Euthyroidism Using 3 Different Regimens of Levothyroxine Intake during the Fasting Month of Ramadan

Abstract: <b><i>Introduction:</i></b> Millions of Muslim hypothyroid patients fast during Ramadan. Limited data are available on the effect of fasting during Ramadan and different levothyroxine (L-T4) timings on thyroid status. The present study aimed to report preference, adherence, and maintenance of euthyroidism using 3 different regimens of L-T4 intake during Ramadan. <b><i>Methods:</i></b> This is a prospective study including Muslim hypothyroid patients fasting durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Post-Ramadan euthyroidism rate of 74% was previously reported by our institution in Ramadan 2018 and 2019 using the same L-T4 regimens used in the present study. [ 12 ] Sheikh et al . [ 14 ] and El-Kaissi et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-Ramadan euthyroidism rate of 74% was previously reported by our institution in Ramadan 2018 and 2019 using the same L-T4 regimens used in the present study. [ 12 ] Sheikh et al . [ 14 ] and El-Kaissi et al .…”
Section: Discussionmentioning
confidence: 99%
“…An adherence rate of 82% was previously reported by our institution in Ramadan 2018 and 2019 using the same L-T4 regimens used in the present study. [ 12 ] Karoli et al . [ 5 ] reported that only 25% of their patients adhered to stopping food 2 h before bedtime L-T4 dosing, while Sheikh et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were free to follow one of three L-T4 regimens during Ramadan, explained in detail previously [ 6 ]. In short, regimen 1: to take L-T4 60 min before Iftar and beverages, regimen 2: to take L-T4 3–4 h after Iftar, 60 min before Suhor meal, regimen 3: to take L-T4 before the start of next fast 3–4 h after an early Suhor around midnight.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting Ramadan entails abstaining from food and drinks from dawn – more than an hour before sunrise – till sundown. In Egypt, years 2018 and 2019, duration of fasting ranged from 15 h:02 min to 15 h:29 min and 14 h:44 min to 15 h:23 min respectively, leaving only 9 h or less for 2 main meals and L-T4 intake for hypothyroid patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%